The Human Body and the Environment - Stewart, T. D. (1955)
The intended purpose of physical anthropology is to gain perspective on the origin of man and his evolution. Those engaged in this field can be better known in more utilitarian science, but become physical anthropologists when seeking a broader perspective of man. This perspective is intriguing but difficult to obtain. Without it, local investigator often loses the broader phenomenon surrounding meaning; with it maybe you can explain a segment of the evolution of man.